Fattening yearling heifers for the summer market. - Weber, A.D. (Kansas Agricultural Experiment Station, 2012)
In tests conducted at the Kansas Agricultural Experiment Station previous to the one reported herein, it was found that heifer calves fed 4 to 5 pounds of grain per head daily during the winter were too fleshy to turn on pasture, hence they could not be used advantageously for deferred full feeding in accordance with the system developed for steer calves. It may be noted in this connection that the standard system approved for good to choice steer calves consists of three phases: (1) producing 225 to 250 pounds of gain during the winter, which usually necessitates the feeding of 4 to 5 pounds of grain per head daily; (2) grazing 90 days without grain; and (3) full feeding 100 days in a dry lot.
Keywords: Beef; Heifers; Summer; Market; Gain